The role of business transformation strategy in Indonesian regional development banks - Audy Thuda; Mohammad Hamsal; Dezie Leonarda Warganegara; Pantri Heriyati (Banks and Bank Systems)
Rapid advances in technology and shifting customer expectations have intensified competition in the financial industry, forcing Indonesia’s banking sector to adopt adaptive and innovative strategies to remain competitive in an increasingly complex and uncertain environment. This study investigates the role of business transformation strategy in organizational performance. Employing a quantitative approach using Structural Equation Modeling (SEM), the study analyzes data collected from 255 Branch Managers across 27 Regional Development Banks in Indonesia. The coefficient of determination for the business transformation strategy was 0.69, indicating that 69% of its variance could be explained by environmental dynamism, transformational leadership, talent development, and digital adoption. Similarly, the R2 value for organizational performance was 0.51, indicating that digital adoption and business transformation strategy accounted for 51% of its variance. The findings reveal that environmental dynamism (t-value 1.85) and talent development (t-value 1.58) do not positively affect business transformation strategy. Instead, transformational leadership (t-value 2.38) and digital adoption (t-value 4.28) positively affect business transformational strategy. Furthermore, business transformation strategy (t-value 3.10) positively affects organizational performance. Meanwhile, business transformation strategy does not mediate the influences of environmental dynamism, talent development, and transformational leadership on organizational performance but strongly mediates digital adoption. This study emphasizes that business transformation strategy is the cornerstone for aligning digital adoption and leadership approaches to drive organizational performance. This study contributes to understanding business transformation strategy in the banking industry by providing technology-driven strategic insights from Indonesian Regional Development Banks.